BENTONITE APPLICATIONS IN SIMPLE PURIFICATION OF BULK COOKING OIL AS ALTERNATIVE SOLUTIONS FOR HOUSEHOLD COST EFFICIENCY - Mira Meirawaty; Christin Palit; Dyah Ayu Setyorini; Moehammad Ali Jambak (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2021)
Utilization of Crude Palm Oil (Crude Palm Oil) in food cooking activities is a strong activity in Indonesian society, more than 80% of household activities use this type of oil to process food ingredients. The affordable price with a variety of packaging makes this type of cooking oil has many fans. A survey that has been conducted on residents of the Kalideres area with a total of 20 respondents stated that in addition to using new palm cooking oil in cooking activities, the majority of residents are also accustomed to using this oil used in cooking activities that require the deep-fried method. The quality of cooking oil is largely determined by the level of purity of the solution, the clearer the color of the solution, the better the quality, the darker the color of the solution indicates the presence of more impurities, the higher the saturated fatty acid emulsion, indicating poor cooking oil quality. This is what was raised in this community service (CS) activity, namely socializing alternatives to the use of purified bulk cooking oil. The purification material uses bentonite clay minerals which are heated and dissolved in a certain amount and duration of time which is able to maximize the adsorption power of impurities according to the natural structure of bentonite. CS activities carried out online include counseling and training activities for housewives in the economically densely populated Kalideres area. Through the socialization program for the purification of bulk cooking oil using bentonite clay minerals, it is hoped that residents will have an alternative to reduce the cost of processing food raw materials in a more effective and healthy way. This program is also expected to function as a medium to socialize the application of earth science in helping activities of daily living.